Zinc-based coated steel sheet with excellent delayed fracture resistance and manufacturing method thereof
Patent Information
- Application Number
- JP2022135240
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-08-26
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2042-08-26
Smart Images

Figure 0007652155000003 
Figure 0007652155000004 
Figure 0007652155000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a zinc-based coated steel sheet used in automobiles, building materials, etc., which has a delayed fracture resistance of 1180 MPa (approximately 120 kgf / mm 2 The present invention relates to a high-strength surface-treated zinc-based plated steel sheet having a tensile strength of at least 1000 g / m2 and a method for manufacturing the same. [Background technology]
[0002] In recent years, in the automotive field, there has been a demand for reducing CO2 emissions by reducing the weight of vehicle bodies from the perspective of environmental protection. In addition, there is a demand for improving collision safety from the perspective of passenger protection, and efforts are being made to increase the strength of steel sheets for automobiles. However, it is known that increasing the strength of steel materials makes them more susceptible to a phenomenon called delayed fracture. Delayed fracture is a phenomenon in which brittle fracture occurs suddenly without plastic deformation after a certain period of time has passed when high-strength steel materials are subjected to a static load stress (load stress less than the tensile strength).
[0003] It is known that delayed fracture is caused by hydrogen that penetrates into steel from the environment (hydrogen embrittlement), and hydrogen can penetrate through the pickling process, wet plating process, and atmospheric corrosion during the manufacturing and processing of steel sheets. Non-Patent Document 1 reports that hydrogen embrittlement susceptibility increases with increasing steel strength, and is prominent in high-strength steels with tensile strengths of 1200 MPa or more, regardless of whether the amount of added alloy elements is increased or decreased. Non-Patent Document 2 reports that hydrogen cracking occurs in high-strength cold-rolled steel sheets with tensile strengths of 1180 MPa class under certain processing conditions and with certain amounts of hydrogen penetration. Zinc-coated steel sheets are widely used for components that require corrosion resistance in atmospheric environments. This is because zinc has excellent sacrificial corrosion protection properties. However, a hydrogen generation reaction occurs on the base steel as a counter reaction to the sacrificial corrosion reaction, so delayed fracture is a major concern for high-strength zinc-coated steel sheets.
[0004] In order to prevent such delayed fracture in high strength steel sheets, for example, Patent Document 1 has investigated weakening the delayed fracture susceptibility by adjusting the structure and alloy components of the steel sheet, and the following has been proposed in mass %: C: 0.07-0.25%, Si: 0.3-2.50%, Mn: 1.5-3.0%, Ti: 0.005-0.09%, B: 0.0001-0.01%, P: 0.001-0.03%, S: 0.0001-0.01%, Al: 2.5% or less, N: 0.000 A high-strength steel sheet with a tensile maximum strength of 900 MPa or more and good ductility and delayed fracture resistance properties has been proposed, which contains Cr:0.5-0.0100%, O:0.0005-0.007%, and the balance is iron and unavoidable impurities, and the steel sheet structure is mainly ferrite and contains martensite composed of block sizes of 1 μm or less, the volume fraction of ferrite is 50% or more, the C concentration in the martensite is 0.3%-0.9%, and the yield ratio (YR) is 0.75 or less. However, the method of this Patent Document 1 does not change the amount of hydrogen that penetrates into the steel sheet from the external environment, so it is possible to delay the occurrence of delayed fracture, but it is not possible to prevent delayed fracture itself. Furthermore, there is a concern that the weldability will deteriorate due to the increase in alloying components.
[0005] Surface treatment of steel sheets has been studied as a method for preventing hydrogen from penetrating into steel. For example, Patent Document 2 studies preventing hydrogen embrittlement by providing a base coat layer made of a resin composition containing vanadium oxide and / or molybdenum oxide and a top coat layer made of a resin composition containing copper oxide on the surface of the steel material. However, the technology described in Patent Document 2 is limited to corrosion in an environment where hydrogen sulfide is present, and does not take into consideration corrosion in an atmospheric corrosive environment.
[0006] As surface treatment techniques for preventing hydrogen penetration in atmospheric corrosive environments, there have been proposed a technique for coating the surface of a steel sheet with a film containing fine particles of one or more elements selected from Mg, Ti, V, Zr, La, Fe, Si, Mo, and Ni, or a compound containing two or more of these elements (Patent Documents 3 to 5); a technique for forming a film consisting of a conductive polymer and an anion on the surface of a steel sheet after pickling treatment (Patent Document 6); a technique for forming a film on the surface of a steel sheet containing one or more metal acid salts selected from Mo salts, W salts, Ca salts, and Be salts, and a P compound (Patent Documents 7 and 8); and a technique for forming a film on the surface of a steel sheet having a lower layer film containing an anionic compound having pH buffer properties and preferably containing one or more metals selected from Al, Mg, Ca, Zn, V, and Mo, and an organic resin containing or not containing an anionic compound in an upper layer (Patent Document 9). However, the coatings formed by these techniques are mainly applied to the surface of cold-rolled steel sheets, and it is unclear whether they are effective for galvanized steel sheets, which are more susceptible to hydrogen penetration than cold-rolled steel sheets in atmospheric corrosive environments.
[0007] As a surface treatment technology for preventing hydrogen penetration into galvanized steel sheets in an atmospheric corrosive environment, for example, a chemical conversion coating layer containing bismuth has been formed on the surface of a galvanized high-strength steel sheet to suppress hydrogen generation on the steel sheet surface (Patent Document 10). However, bismuth is very expensive, which raises the problem of high manufacturing costs. In addition, a technology has been proposed for suppressing hydrogen penetration by forming a zinc-nickel-based plating layer on the surface of a high-strength steel sheet in which Ni is added during plating (Patent Document 11). However, this technology is difficult to apply to hot-dip galvanized steel sheets, which are widely used in the fields of automobiles and building materials, because the plating is formed by an electroplating process. In addition, although the techniques of the above-mentioned patent documents are effective at temperatures above room temperature, it is unclear whether they are effective in low-temperature environments such as cold regions. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2011-111671 A [Patent Document 2] Japanese Patent Application Publication No. 2-21970 [Patent Document 3] JP 2003-41384 A [Patent Document 4] JP 2016-160507 A [Patent Document 5] JP 2017-2354 A [Patent Document 6] JP 2018-44240 A [Patent Document 7] JP 2018-109216 A [Patent Document 8] JP 2018-168467 A [Patent Document 9] JP 2018-188707 A [Patent Document 10] JP 2015-209585 A [Patent Document 11] JP 2019-26893 A [Non-patent literature]
[0009] [Non-Patent Document 1] "Delayed Fracture" by Shinsaku Matsuyama, Nikkan Kogyo Shimbun, 1989 [Non-Patent Document 2] Yuki Taji and 4 others, "Evaluation Method of Hydrogen Embrittlement Resistance of High Strength Thin Steel Plates," Iron and Steel Institute of Japan, Vol. 95, No. 12, pp. 887-894, 2009 Summary of the Invention [Problem to be solved by the invention]
[0010] Therefore, an object of the present invention is to solve the above-mentioned problems of the conventional art and to provide a zinc-based plated steel sheet (surface-treated zinc-based plated steel sheet) which has excellent delayed fracture resistance regardless of the composition of the base steel sheet and can be produced at low cost, and a production method thereof. [Means for solving the problem]
[0011] In order to solve the above problems, the present inventors have conducted extensive research and studies into means for suppressing hydrogen penetration by surface treatment of steel sheet, and have found that delayed fracture of steel sheet can be effectively suppressed by forming a coating containing hypophosphite on a zinc-based plated steel sheet. The present invention has been made based on these findings, and has the following gist.
[0012] [1] A steel sheet having a tensile strength of 1180 MPa or more, a zinc-based plating layer formed on at least one surface of the steel sheet, and a coating containing hypophosphite formed on the surface of the zinc-based plating layer, wherein the coating has a coating weight of hypophosphite of 0.01 to 2 g / m 2 A zinc-based plated steel sheet comprising: [2] A steel sheet having a tensile strength of 1180 MPa or more, a zinc-based plating layer formed on at least one surface of the steel sheet, and an organic resin coating or an inorganic coating containing hypophosphite formed on the surface of the zinc-based plating layer, the content of hypophosphite in the coating being 10 to 50 mass % and the coating weight of hypophosphite being 0.01 to 2 g / m 2 A zinc-based plated steel sheet comprising: [3] A steel sheet having a tensile strength of 1180 MPa or more, a zinc-based plating layer formed on at least one surface of the steel sheet, an underlayer coating containing hypophosphite formed on the surface of the zinc-based plating layer, and an organic resin coating formed on the upper layer of the underlayer coating, wherein the hypophosphite content in the underlayer coating is 10 to 50 mass % and the coating weight of the hypophosphite is 0.01 to 2 g / m 2 A zinc-based plated steel sheet comprising:
[0013] [4] A steel sheet having a tensile strength of 1180 MPa or more, a zinc-based plating layer formed on at least one surface of the steel sheet, an underlayer coating formed on the surface of the zinc-based plating layer, and an organic resin coating containing hypophosphite formed on the underlayer coating, wherein the content of hypophosphite in the organic resin coating is 10 to 50 mass % and the coating weight of hypophosphite is 0.01 to 2 g / m 2 A zinc-based plated steel sheet comprising: [5] A steel sheet having a tensile strength of 1180 MPa or more, a zinc-based plating layer formed on at least one surface of the steel sheet, an underlayer coating containing hypophosphite formed on the surface of the zinc-based plating layer, and an organic resin coating containing hypophosphite formed on the underlayer coating, wherein the hypophosphite contents in the underlayer coating and the organic resin coating are each 10 to 50 mass %, and the total coating weight of hypophosphite in the underlayer coating and the organic resin coating is 0.01 to 2 g / m 2 A zinc-based plated steel sheet comprising:
[0014] [6] The zinc-based plated steel sheet according to any one of the above [2] to [5], characterized in that the organic resin constituting the organic resin coating is one or more selected from the group consisting of epoxy resin, acrylic resin, urethane resin, ethylene resin, phenolic resin, polyester resin, fluororesin, polyolefin resin, and epoxy ester resin. [7] The zinc-based plated steel sheet according to any one of the above [1] to [6], characterized in that the hypophosphite is at least one selected from the group consisting of sodium hypophosphite, potassium hypophosphite, nickel hypophosphite, calcium hypophosphite, magnesium hypophosphite, and manganese hypophosphite.
[0015] [8] A zinc-based plated steel sheet having a tensile strength of 1180 MPa or more and a zinc-based plated layer formed on at least one surface of the steel sheet is used as a substrate, and a treatment liquid containing hypophosphite is applied to the surface of the zinc-based plated layer, followed by drying to form a coating containing hypophosphite, and the coating has an adhesion amount of hypophosphite of 0.01 to 2 g / m 21. A method for producing a zinc-based plated steel sheet, comprising the steps of: [9] A zinc-based plated steel sheet having a tensile strength of 1180 MPa or more and a zinc-based plated layer formed on at least one surface of the steel sheet is used as a substrate, and an organic resin-based or inorganic-based treatment liquid containing hypophosphite is applied to the surface of the zinc-based plated layer, and then dried to form an organic resin film or an inorganic-based film containing hypophosphite, and the content of hypophosphite in the film is 10 to 50 mass% and the amount of hypophosphite attached is 0.01 to 2 g / m 2 1. A method for producing a zinc-based plated steel sheet, comprising the steps of:
[0016]
[10] A method for manufacturing a steel sheet having a tensile strength of 1180 MPa or more, on at least one surface of which a zinc-based plating layer is formed, comprising: a zinc-based plating layer having a tensile strength of 1180 MPa or more; a treatment liquid containing hypophosphite is applied to the surface of the zinc-based plating layer, and the treatment liquid is dried to form an underlayer coating containing hypophosphite; and an organic resin coating is formed on the underlayer coating by applying an organic resin treatment liquid to the surface of the underlayer coating and drying the organic resin coating; and the hypophosphite content in the underlayer coating is 10 to 50 mass% and the amount of hypophosphite attached is 0.01 to 2 g / m. 2 1. A method for producing a zinc-based plated steel sheet, comprising the steps of:
[11] A zinc-based plated steel sheet having a tensile strength of 1180 MPa or more and a zinc-based plating layer formed on at least one surface of the steel sheet is used as a substrate, a treatment liquid is applied to the surface of the zinc-based plating layer and dried to form an underlayer coating, and then an organic resin-based treatment liquid containing hypophosphite is applied to the surface of the underlayer coating and dried to form an organic resin coating containing hypophosphite on the upper layer of the underlayer coating, and the content of hypophosphite in the organic resin coating is 10 to 50 mass% and the amount of hypophosphite attached is 0.01 to 2 g / m 2 1. A method for producing a zinc-based plated steel sheet, comprising the steps of:
[0017]
[12] A method for manufacturing a steel sheet having a tensile strength of 1180 MPa or more, on at least one surface of which a zinc-based plating layer is formed, comprising: applying a treatment liquid containing hypophosphite to the surface of the zinc-based plating layer and drying the same to form an underlayer coating containing hypophosphite; applying an organic resin-based treatment liquid containing hypophosphite to the surface of the underlayer coating and drying the same to form an organic resin coating containing hypophosphite on the upper layer of the underlayer coating; and a method for manufacturing a steel sheet having a tensile strength of 1180 MPa or more and a zinc-based plating layer on which a hypophosphite-containing underlayer coating is formed. 2 1. A method for producing a zinc-based plated steel sheet, comprising the steps of:
[0018]
[13] A method for producing a zinc-based plated steel sheet according to any one of the above [9] to
[12] , characterized in that the organic resin constituting the organic resin coating is one or more selected from the group consisting of epoxy resin, acrylic resin, urethane resin, ethylene resin, phenolic resin, polyester resin, fluororesin, polyolefin resin and epoxy ester resin.
[14] The method for producing a zinc-based plated steel sheet according to any one of the above [8] to
[13] , characterized in that the hypophosphite is at least one selected from the group consisting of sodium hypophosphite, potassium hypophosphite, nickel hypophosphite, calcium hypophosphite, magnesium hypophosphite and manganese hypophosphite.
[15] A surface treatment solution for forming a coating on a surface of a zinc-based plated steel sheet to suppress delayed fracture of the zinc-based plated steel sheet having a tensile strength of 1180 MPa or more, the surface treatment solution containing hypophosphite. Effect of the Invention
[0019] The zinc-based plated steel sheet of the present invention has an excellent delayed fracture resistance property in which delayed fracture is effectively suppressed by forming a coating containing a specific component on its surface, and has an advantage that this excellent delayed fracture resistance property can be obtained regardless of the composition of the base steel sheet. In addition, the zinc-based plated steel sheet of the present invention can be manufactured at low cost because it does not use expensive materials such as bismuth for the surface coating. Therefore, it is a surface-treated zinc-based plated steel sheet suitable for automobiles and building materials, and weight reduction is possible by using high-strength materials in these applications. Moreover, according to the manufacturing method of the present invention, it is possible to appropriately manufacture a zinc-based plated steel sheet having the above-mentioned excellent delayed fracture resistance at low cost. [Brief description of the drawings]
[0020] [Figure 1] FIG. 3 is a plan view showing a test piece obtained by processing a zinc-coated steel sheet, which constitutes the test piece for evaluating delayed fracture resistance in FIG. 2. [Diagram 2] Schematic diagram of test specimens for evaluating delayed fracture resistance used in the examples. [Diagram 3] FIG. 1 is an explanatory diagram showing the steps of a combined cycle corrosion test simulating corrosion in a low-temperature environment performed in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The steel sheet serving as the base material (substrate) of the surface-treated zinc-plated steel sheet having excellent delayed fracture resistance of the present invention is a high-strength steel sheet having a tensile strength of 1180 MPa or more, and more preferably a high-strength steel sheet having a tensile strength of 1470 MPa or more. A steel sheet having a low tensile strength is inherently less susceptible to delayed fracture. The effect of the present invention is also exhibited in a steel sheet having a low tensile strength, but is significantly exhibited in a steel sheet having a tensile strength of 1180 MPa or more, and is more significantly exhibited in a steel sheet having a tensile strength of 1470 MPa or more. There are no particular limitations on the chemical composition or steel structure.
[0022] The high-strength steel sheet preferably used in the present invention may have any composition and structure as long as it has the desired tensile strength. In order to improve various properties such as mechanical properties, for example, solid solution strengthening by adding interstitial solid solution elements such as C and N and substitutional solid solution elements such as Si, Mn, P, and Cr, precipitation strengthening by carbonitrides such as Ti, Nb, V, and Al, and chemical composition modification such as adding strengthening elements such as W, Zr, B, Cu, and rare earth elements can be performed. In addition, toughening can be performed by recovery annealing at a temperature where recrystallization does not occur, or partial recrystallization strengthening can be performed by leaving unrecrystallized regions without completely recrystallizing. In addition, strengthening by transformation structure such as bainite or martensite single phase or a composite structure of ferrite and these transformation structures, and strengthening by the Hall-Petch formula: σ=σ0+kd where ferrite grain size is d. -1 / 2 (where σ is stress, σ0, k are material constants) and processing strengthening by rolling, etc. These structural or textural modifications can be carried out alone or in combination.
[0023] The composition of such a high-strength steel plate may contain, for example, 0.1-0.4 mass% C, 0-2.5 mass% Si, 1-3.5 mass% Mn, 0-0.05 mass% P, 0-0.005 mass% S, with the balance being Fe and unavoidable impurities. The chemical composition of the steel sheet may further include, as an optional element, one or more selected from the group consisting of Cu: 1.0 mass% or less, Ti: 0.2 mass% or less, V: 0.5 mass% or less, sol. Al: 0.1 mass% or less, Cr: 1.0 mass% or less, Nb: 0.2 mass% or less, W: 0.5 mass% or less, Zr: 0.1 mass% or less, B: 0.005 mass% or less, N: 0.0005 to 0.0100 mass%, Ni: 0.01 to 2.00 mass%, Mo: 0.005 to 2.000 mass%, Ca: 0.0002 to 0.0050 mass%, REM: 0.0002 to 0.0050 mass%, Sb: 0.002 to 0.200 mass%, and Sn: 0.002 to 0.200 mass%. In general, it is preferable that these optional elements are added up to a total amount of about 4 mass%. The lower limit of the content of each element is preferably about 0.01 mass% for Si, sol.Al, and Cr, about 0.005 mass% for Cu, Ti, V, Nb, W, and Zr, about 0.001 mass% for P, and about 0.0001 mass% for B and S.
[0024] In addition, examples of commercially available high-strength steel sheets include, but are not limited to, JFE-CA1180, JFE-CA1320, JFE-CA1470, JFE-CA1180SF, JFE-CA1180Y1, JFE-CA1180Y2 (all manufactured by JFE Steel Corporation), SAFC1180D (manufactured by Nippon Steel Corporation), etc. In addition, both cold-rolled steel sheets and hot-rolled steel sheets can be used as high-strength steel sheets. The thickness of the high-strength steel plate is not particularly limited, but is generally about 0.8 to 5 mm, and more preferably about 1.0 to 2.0 mm. The zinc-based plating that covers the high-strength steel sheet (base steel sheet) is a plating containing zinc as a main component, and may be formed by any plating method such as hot-dip plating, electroplating, electroless plating, or vapor deposition plating. Hot-dip galvanizing also includes alloyed hot-dip galvanizing, which is alloyed after plating. Zinc-based plating also includes zinc alloy plating formed by any plating method such as electroplating, electroless plating, or vapor deposition plating. Examples of zinc alloy plating include zinc-nickel, zinc-manganese, zinc-aluminum, and zinc-aluminum-magnesium plating. The above-mentioned zinc-based plating is formed on at least one surface of a high-strength steel sheet (base steel sheet).
[0025] In the present invention, a coating containing hypophosphite is provided on the surface of the zinc-based plating layer (the zinc-based plating layer formed on at least one surface of the steel sheet) of the above-mentioned zinc-based plated steel sheet, and this coating has a predetermined adhesion amount, thereby suppressing the penetration of hydrogen in a corrosive environment and providing excellent delayed fracture resistance. In general, hydrogen penetration into zinc-based plated steel sheets is largely due to the hydrogen generation reaction on the steel substrate, which occurs as a counter reaction to the sacrificial corrosion protection of zinc during the corrosion process under humid conditions. Therefore, it is believed that suppressing the increase in the exposed steel substrate, which is the hydrogen generation site, leads to the suppression of hydrogen penetration. The hypophosphite added to the coating in the present invention has high reduction reactivity, so it reacts with the steel substrate during the corrosion process under humid conditions to form reducible iron phosphate, which covers the exposed steel substrate, which is the hydrogen generation site, and is therefore believed to lead to the suppression of hydrogen penetration. It is also known that aluminum dihydrogen tripolyphosphate, which has been widely used as a rust prevention additive, has an active ingredient dissolved in the liquid film that acts on other ions coexisting in the corrosive environment to form a salt that is poorly soluble or insoluble in water, which covers the exposed steel substrate. However, since hypophosphite reacts directly with the steel substrate to form reducible iron phosphate, it is believed to have better adhesion to the metal substrate than the coating by the above-mentioned rust prevention additive, and therefore is believed to have a high covering effect on the exposed steel substrate, which is the hydrogen generation site. Examples of hypophosphites contained in the coating include sodium hypophosphite, potassium hypophosphite, nickel hypophosphite, calcium hypophosphite, magnesium hypophosphite, and manganese hypophosphite, and one or more of these can be used.
[0026] There is no limitation on the form in which the hypophosphite-containing coating is formed on the surface of the plated steel sheet, and the coating may contain hypophosphite alone or together with other inorganic components, or may be an organic resin coating containing hypophosphite. In a multi-layer coating consisting of two or more layers, one or more layers may be a hypophosphite-containing coating. Thus, typical forms of the zinc-based plated steel sheet of the present invention include the following. However, the zinc-based plated steel sheet of the present invention is not limited to the following forms, as long as a coating containing hypophosphite is formed in some form.
[0027] (i) A zinc-based plated steel sheet has an inorganic coating containing hypophosphite on the surface of the zinc-based plated layer (a zinc-based plated layer formed on at least one surface of the steel sheet). This inorganic coating contains hypophosphite alone or together with other inorganic components. (ii) The surface of a zinc-based plating layer (a zinc-based plating layer formed on at least one surface of a steel sheet) has an organic resin film containing hypophosphite. This organic resin film contains hypophosphite alone or together with other inorganic components. (iii) A zinc-based plating layer (a zinc-based plating layer formed on at least one surface of a steel sheet) has an underlayer coating containing hypophosphite and an organic resin coating on the underlayer coating. The underlayer coating contains hypophosphite alone or in combination with other inorganic components and / or organic resins. (iv) A zinc-based plating layer (a zinc-based plating layer formed on at least one surface of a steel sheet) has an underlayer coating made of an inorganic component and / or an organic resin, and an organic resin coating containing hypophosphite on the underlayer coating. This organic resin coating contains hypophosphite alone or together with other inorganic components. (v) A zinc-based plating layer (a zinc-based plating layer formed on at least one surface of a steel sheet) has an underlayer coating containing hypophosphite on its surface, and an organic resin coating containing hypophosphite on top of the underlayer coating. The underlayer coating contains hypophosphite alone or together with other inorganic components and / or organic resins, and the organic resin coating contains hypophosphite alone or together with other inorganic components.
[0028] In order for a coating containing hypophosphite to fully exert its effect of suppressing the occurrence of delayed fracture in a corrosive environment, the amount of hypophosphite attached in the coating must be 0.01 to 2 g / m. 2 The amount of hypophosphite applied must be 0.01 g / m 2 If the coating weight is less than 2 g / m, the effect of including hypophosphite in the coating (effect of suppressing delayed fracture) cannot be fully obtained. 2 If the concentration exceeds this range, it is believed that an increased amount of active ingredients will leach out from the hypophosphite in the coating into the water film, forming phosphate compounds with ions in the water film and precipitating on the steel substrate, with the result that the amount of reaction between the base steel sheet and the hypophosphite will decrease, resulting in a decrease in the amount of reducible iron phosphate formed. In the case of a multi-layer coating consisting of two or more layers of films, when two or more layers of films contain hypophosphite, the amount of hypophosphite attached is the total amount of hypophosphite contained in the two or more layers of films.
[0029] The amount of hypophosphite attached can be adjusted by adjusting the concentration of the treatment liquid or the amount of the treatment liquid applied when the treatment liquid is applied to the surface of the plated steel sheet to form a film containing hypophosphite. In addition, when the hypophosphite is contained in the coating together with other inorganic and / or organic components, the content of the hypophosphite in the coating is 10 to 50 mass%, preferably 30 to 50 mass% from the viewpoint of suppressing delayed fracture. When the hypophosphite is contained in the coating together with other inorganic and / or organic components, the hypophosphite is one of the factors that determine the lubricity of the coating, so if the content is less than 10 mass%, the lubricity of the coating may decrease. In addition, if the content exceeds 50 mass%, the water resistance after painting may decrease.
[0030] Examples of organic resins constituting the organic resin film include epoxy resins, acrylic resins, urethane resins, ethylene resins, phenolic resins, and polyester resins, and one or more types selected from these can be used. Regardless of whether the organic resin film contains hypophosphite or not, if the film thickness is small, the function as a barrier layer against a corrosive environment is reduced, so the film thickness is preferably 0.1 μm or more. On the other hand, in the case of steel sheets for automobiles, after being processed into a predetermined shape by pressing, there is a process of assembling the steel sheets by spot welding. In this case, if the organic resin film is too thick, the current during welding may not flow, resulting in poor welding, so in applications where spot welding is used to join steel sheets, the film thickness of the organic resin film is preferably 4.0 μm or less.
[0031] The amount of hypophosphite attached in the coating can be calculated, for example, by irradiating the coating surface with X-rays, measuring the intensity of the fluorescent X-rays of the elements contained in the hypophosphite, and comparing it with a calibration curve. In addition, in the case of a multi-layer coating, the total amount of hypophosphite attached is measured by fluorescent X-rays, and then, if the upper layer is an organic coating, the upper layer coating is dissolved using an organic solvent (e.g., acetone, etc.), and the amount of hypophosphite attached in the state of only the lower layer coating is measured, thereby obtaining the amount of hypophosphite attached in the lower layer coating. In addition, in the case of an inorganic coating, the upper layer coating is removed by buffing, and the amount of hypophosphite attached in the state of only the lower layer coating is measured, thereby obtaining the amount of hypophosphite attached in the lower layer coating. In either case, the amount of hypophosphite attached in the upper layer coating can be obtained by taking the difference between the total amount of hypophosphite attached and the amount of hypophosphite attached in the lower layer coating.
[0032] The content of hypophosphite in the coating can be calculated, for example, by dividing the amount of hypophosphite attached by the amount of hypophosphite attached to the entire coating. The amount of hypophosphite attached to the entire coating can be calculated, for example, by measuring the mass of the steel sheet with and without the coating attached, and dividing the difference between the measured amounts by the area of the steel sheet. It can also be calculated by measuring the intensity of fluorescent X-rays of elements contained in the coating and comparing it with a calibration curve. Examples of elements contained in the coating include carbon in the case of an organic coating, and silicon and phosphorus in the case of an inorganic coating. In addition, in the case of a multi-layer coating, the hypophosphite content in the lower layer coating is obtained by dividing the amount of hypophosphite attached in the lower layer coating by the amount of hypophosphite attached in the upper layer coating, and the hypophosphite content in the upper layer coating is obtained by dividing the amount of hypophosphite attached in the upper layer coating by the amount of hypophosphite attached in the upper layer coating. The amounts of the upper layer coating and the lower layer coating can be calculated, for example, by measuring the intensity of fluorescent X-rays of elements contained in the coating and comparing it with a calibration curve. Examples of elements contained in the coating include carbon in the case of an organic coating, and silicon and phosphorus in the case of an inorganic coating. When the elements to be measured are mixed in each layer and cannot be separated and quantified in each layer, the amount of adhesion of the lower coating can be measured by removing the upper coating. For example, when the upper coating is an organic coating, the upper coating is dissolved using an organic solvent (e.g., acetone, etc.), and when the upper coating is an inorganic coating, the upper coating is removed by buffing. When it is difficult to use fluorescent X-rays in terms of measurement accuracy, the amount of adhesion of the lower coating after the upper coating is removed can be measured by measuring the cross-sectional thickness using a scanning electron microscope and estimating it from the density of the coating. The amount of adhesion of the upper coating can also be obtained by measuring the mass of the steel sheet before and after the removal of the upper coating, and dividing the difference in the measured amount by the area of the steel sheet. The thickness of the organic resin film is measured by observing the cross section of the film, measuring the thickness of the film (from the zinc-based plated steel sheet surface of the substrate to the film surface) at multiple points (e.g., three points) in an arbitrary field of view, and averaging these values to determine the film thickness. The method of processing the cross section is not particularly limited, but examples include FIB (Focused Ion Beam) processing.
[0033] Next, the method for producing a zinc-based plated steel sheet of the present invention will be described. A treatment solution containing hypophosphite is applied to the surface of the zinc-based plated steel sheet (a zinc-based plating layer formed on at least one surface of the steel sheet) which is the substrate as described above, and then dried to produce a zinc-based plated steel sheet containing hypophosphite and having a coating weight of 0.01 to 2 g / m as described above. 2 A film is formed. When forming an inorganic coating containing hypophosphite, an inorganic coating such as an aqueous coating containing hypophosphite is used as the treatment liquid. When forming an organic resin coating containing hypophosphite, an organic resin coating such as an aqueous resin solution or an organic solvent resin solution containing hypophosphite is used. Therefore, the following are representative forms of the manufacturing method of the present invention. However, the manufacturing method of the present invention is not limited to the following forms, as long as a coating containing hypophosphite is formed by applying and drying some kind of treatment liquid.
[0034] (i) An inorganic coating containing hypophosphite is formed on the surface of a zinc-based plating layer by applying an inorganic treatment solution containing hypophosphite and drying the solution. This inorganic coating contains hypophosphite alone or together with other inorganic components. (ii) A hypophosphite-containing organic resin coating is formed on the surface of a zinc-based plating layer by applying an organic resin-based treatment liquid containing hypophosphite and drying the liquid. This organic resin coating contains hypophosphite alone or together with other inorganic components. (iii) A treatment liquid containing hypophosphite is applied to the surface of a zinc-based plating layer and dried to form an underlayer coating containing hypophosphite, and then an organic resin treatment liquid is applied to the surface of the underlayer coating and dried to form an organic resin coating on the underlayer coating. The underlayer coating contains hypophosphite alone or together with other inorganic components and / or organic resins.
[0035] (iv) A treatment liquid is applied to the surface of a zinc-based plating layer and dried to form an underlayer coating (an underlayer coating consisting of an inorganic component and / or an organic resin), and then an organic resin-based treatment liquid containing hypophosphite is applied to the surface of this underlayer coating and dried to form an organic resin coating containing hypophosphite on the upper layer of the underlayer coating. This organic resin coating contains hypophosphite alone or together with other inorganic components. (v) A treatment liquid containing hypophosphite is applied to the surface of a zinc-based plating layer and dried to form an underlayer coating containing hypophosphite, and then an organic resin-based treatment liquid containing hypophosphite is applied to the surface of this underlayer coating and dried to form an organic resin coating containing hypophosphite on the underlayer coating. The underlayer coating contains hypophosphite alone or together with other inorganic components and / or organic resins, and the organic resin coating contains hypophosphite alone or together with other inorganic components.
[0036] The treatment solution may be applied to the surface of the plated steel sheet by any of the following methods: coating (bar coating), spraying, and immersion (and roll squeezing). After application, the sheet is heated and dried using a heating means such as an induction heater at a sheet temperature of about 70 to 250°C. In the case of a multi-layer coating consisting of two or more layers, the treatment liquid is applied and heated and dried for each layer in the manner described above. The amount of hypophosphite attached in the coating is adjusted by adjusting the concentration of the treatment liquid, adjusting the amount of treatment liquid applied, or the like. The surface treatment liquid of the present invention is a surface treatment liquid for forming a coating on the surface of a zinc-based plated steel sheet for suppressing delayed fracture of the zinc-based plated steel sheet having a tensile strength of 1180 MPa or more, and contains hypophosphite. When the surface treatment solution contains inorganic components and organic resins other than the hypophosphite, the ratio of the hypophosphite in the total solid content of the surface treatment solution (ratio to the total solid content mass) is preferably 10 to 50 mass%, more preferably 30 to 50 mass%, for the same reasons as those for the high-strength galvanized steel sheet explained above. EXAMPLES
[0037] A galvannealed steel sheet was used as the base material, a zinc-based plated steel sheet. The base steel sheet of this galvannealed steel sheet had a chemical composition of C: 0.22 mass%, Si: 1.2 mass%, Mn: 3.0 mass%, P: 0.007 mass%, S: 0.0005 mass%, with the balance being Fe and unavoidable impurities, and had a tensile strength of 1580 MPa and a sheet thickness of 1.4 mm. This galvannealed steel sheet (double-sided plated steel sheet) had a coating weight of 44 g / m per side. 2 The Fe content of the zinc plating film was 14 mass %. This galvannealed steel sheet was immersed in toluene and subjected to ultrasonic cleaning for 5 minutes to remove the rust-preventive oil, and used as a test material.
[0038] A coating containing a phosphate (hypophosphite or orthophosphate) shown in Tables 1 and 2 was formed on this test material. In the case of coatings containing phosphate alone, phosphate was added (mixed) to deionized water to make the treatment liquid (treatment liquids marked with * in Tables 1 and 2), which was applied to the surface of the test material using a bar coater, and then heated and dried using an induction heater so that the sheet temperature reached was 140°C, forming a film. Note that No. 7 in Table 1 is a case where a coating containing sodium borate alone, rather than phosphate, was formed, and the film was formed in accordance with the above method. In the case of an inorganic coating containing phosphate, phosphate was added (mixed) to a treatment solution having the composition below in the mass ratio (content) shown in Tables 1 and 2 to obtain treatment solution A. This treatment solution A was applied to the surface of the test material by bar coating, and then heated and dried using an induction heater so that the ultimate sheet temperature reached 140°C to form a film.
[0039] [Composition of processing solution] Component (a): Sodium zirconium carbonate 20% by mass Component (b): Tetraethoxysilane 1.68% by mass Component (c): Polyethylene glycol diglycidyl ether 0.43% by mass Component (d): 1-hydroxymethane-1,1-diphosphonic acid (9) + tartaric acid (1) 1.22% by mass (however, the numbers in parentheses indicate the mass ratio) Component (e): Sodium metavanadate 0.34% by mass Component (f): Ammonium titanium fluoride 0.07% by mass
[0040] In the case of an organic resin film containing phosphate, phosphate was added (mixed) to any of the resin solutions B1 to B5 below in the mass ratio (content) shown in Tables 1 and 2 to prepare treatment solutions B1 to B5. These treatment solutions B1 to B5 were applied to the surface of the test material by bar coating, and then heated and dried with an induction heater so that the ultimate sheet temperature reached 140°C to form a film. B1: Epoxy resin (Japan Epoxy Resin Co., Ltd., product name: jER1009) B2: Acrylic resin (manufactured by DIC Corporation, product name: 40-418EF) B3: Urethane resin (manufactured by Dai Nippon Paint Co., Ltd., product name: V Top RC Clear) B4: Fluorine resin (manufactured by Asahi Glass Co., Ltd., product name: Lumiflon LF552) B5: Epoxy ester resin (manufactured by DIC Corporation, product name: Watersol EFD-5560) For all of the coatings described above, the amount of phosphate attached in the coating was adjusted by adjusting the phosphate concentration in the treatment solution (the same was true for sodium borate No. 7).
[0041] For each of the zinc-plated steel sheets obtained as described above, the film structure was measured and the following properties were evaluated. The results are shown in Tables 1 and 2 together with the film structure. The amount of phosphate attached in the film was measured by measuring the amount of P before and after applying the film using fluorescent X-rays, and the amount of phosphate attached was calculated from the difference between the measured amounts. The amount of sodium borate attached in the film was measured by measuring the amount of B before and after applying the film using fluorescent X-rays, and the amount of sodium borate attached was calculated from the difference between the measured amounts. In measuring the phosphate content in the coating, the mass of the steel sheet before and after application of the coating was measured, the difference between the measured masses was divided by the steel sheet area to calculate the total coating adhesion amount, and the phosphate content was calculated by dividing the adhesion amount of hypophosphite by the total coating adhesion amount. The thickness of the coating was measured by observing the cross section obtained by FIB processing with an SEM, measuring the thickness of the coating (thickness from the base plated steel sheet surface to the surface of the organic resin coating) at three points in an arbitrary field of view, and averaging these values to obtain the coating thickness. The coating weight was measured by measuring the mass of the steel sheet before and after application of the coating, and calculating the difference between the measured masses by the area of the steel sheet.
[0042] (1) Evaluation of delayed fracture resistance The galvanized steel sheets of the invention and comparative examples were each sheared to a size of 35 mm wide x 100 mm long, and then ground to a width of 30 mm to remove residual stress during shearing, and holes were drilled to attach bolts to prepare test pieces as shown in FIG. 1 (dimensions in the figure are in mm). The test pieces were bent at 90° using a three-point bending tester so that the bending radius was 10 mm. As shown in FIG. 2, the shape of the test piece 1 was fixed using a bolt 2 (size: M8) and a nut 3 (size: M8) so that the difference in the inner spacing of the flange ends was 14 mm before and after restraint, and a test piece for evaluating delayed fracture resistance was obtained. The test pieces for evaluating delayed fracture resistance thus prepared were subjected to a dry and wet cycle test shown in FIG. 3, which simulates corrosion in a low-temperature environment, and the test was carried out for up to 28 days. The test temperature was constant (10°C), and the humidity cycle consisted of a total of four steps, including a dry step at a relative humidity of 30%, a wet step at a relative humidity of 90%, and a humidity increase and decrease step, making up one cycle. Each step was switched every 2 hours, and one cycle was repeated for 8 hours. In addition, at the start of the dry step twice a week, the specimens were washed with pure water and then washed with 27 mass% (adherent salt content 1g / m 2) of saline solution was sprayed onto the sample to add chloride. At the start of the drying process every three cycles (every day), the presence or absence of cracks in the bent parts of the test pieces for evaluating delayed fracture resistance was visually confirmed, and the number of days until cracks occurred (hereinafter referred to as "days to crack") was examined. In this test, three specimens were tested for each of the zinc-plated steel sheets of the invention examples and comparative examples, and the delayed fracture resistance was evaluated using the average number of days to crack according to the following criteria, with only ⊚ being deemed to pass. In Tables 1 and 2, the number of days to crack of 29 days indicates that no cracks occurred in the results of this example. ◎: 29 days or more since cracking 〇: The number of days between cracking is 20 or more and less than 29 days. △: Number of days to crack is 10 or more but less than 20 days ×: Less than 10 days after cracking
[0043] (2) Evaluation of corrosion resistance after painting The galvanized steel sheets of the invention and comparative examples were each sheared to a size of 150 mm x 70 mm to obtain flat test pieces, which were used as test pieces for corrosion resistance testing. The test pieces for corrosion resistance testing were subjected to chemical conversion treatment by immersion under standard conditions (35°C, 120 seconds) using "Palbond" manufactured by Nippon Parkerizing Co., Ltd., and then to electrodeposition coating and baking treatment using electrodeposition paint "GT-100" manufactured by Kansai Paint Co., Ltd. The coating thickness of the electrodeposition coating was 15 μm, and the thickness was measured using a commercially available electromagnetic coating thickness meter. After painting, the test pieces were cut with a cutter knife to make an X-cut (crossing angle 60° to 90°) that reached the base material, and a salt spray test specified in JIS Z2371 was performed for 840 hours, and the maximum rust width from the cross cut of the test pieces after the test was measured to evaluate the corrosion resistance. The corrosion resistance was evaluated as follows by calculating the maximum rust width A of each test piece, assuming that the maximum rust width of the steel plate as is was 1, with ⊚ and ◯ being pass marks. ◎:A≦0.8 ○:0.8 <A≦0.95 △:0.95 <A≦1.2 ×:1.2
[0044] In Tables 1 and 2, No. 1 (Comparative Example) is a plated steel sheet on which no hypophosphite-containing coating is formed (Comparative Example of Galvannealed Steel Sheet as is), and it is found that cracks occur early and delayed fracture resistance is poor. Nos. 2 to 4 (Comparative Examples) are surface-treated galvanized steel sheets on which a hypophosphite-free coating is formed in a single layer or two layers. Some of them have slightly improved delayed fracture resistance compared to the plated steel sheet of No. 1, but no sufficient improvement in delayed fracture resistance is observed. Nos. 5 to 12 are surface-treated galvanized steel sheets on which a coating containing zinc phosphate, aluminum phosphate, or sodium borate is formed in a single layer or two layers. Some of them have slightly improved delayed fracture resistance compared to the plated steel sheet of No. 1, but no sufficient improvement in delayed fracture resistance is observed. In contrast, Nos. 13 to 31 (invention examples) are plated steel sheets in which a coating containing hypophosphite is formed in an amount within the range of the present invention, and they have excellent delayed fracture resistance and good corrosion resistance after painting. Nos. 33 and 34 (invention examples) also have excellent delayed fracture resistance, but there is a concern that the sliding properties may deteriorate because the hypophosphite content in the coating is less than 10 mass%. On the other hand, the plated steel sheet No. 32 (comparative example), in which the amount of hypophosphite deposited is outside the range of the present invention, has slightly improved delayed fracture resistance compared to the plated steel sheet No. 1, but has inferior delayed fracture resistance compared to the plated steel sheets Nos. 13, 21, 24, etc., which are invention examples.
[0045] [Table 1]
[0046] [Table 2] [Explanation of symbols]
[0047] 1 Test piece 2 Volts 3 Nut
Claims
1. A steel sheet having a tensile strength of 1180 MPa or more, a zinc-based plating layer formed on at least one surface of the steel sheet, and a coating containing hypophosphite (excluding coatings containing hypophosphite and a magnesium compound) formed on the surface of the zinc-based plating layer, wherein the coating has a coating weight of hypophosphite of 0.01 to 2 g / m 2 A zinc-based plated steel sheet comprising:
2. A steel sheet having a tensile strength of 1180 MPa or more, a zinc-based plating layer formed on at least one surface of the steel sheet, and an organic resin film or an inorganic film containing hypophosphite formed on the surface of the zinc-based plating layer, the content of hypophosphite in the film being 10 to 50 mass % and the coating weight of hypophosphite being 0.01 to 2 g / m 2 A zinc-based plated steel sheet comprising:
3. A steel sheet having a tensile strength of 1180 MPa or more, a zinc-based plating layer formed on at least one surface of the steel sheet, an underlayer coating containing hypophosphite formed on the surface of the zinc-based plating layer, and an organic resin coating formed on the underlayer coating, wherein the hypophosphite content in the underlayer coating is 10 to 50 mass % and the coating weight of the hypophosphite is 0.01 to 2 g / m 2 A zinc-based plated steel sheet comprising:
4. A steel sheet having a tensile strength of 1180 MPa or more, a zinc-based plating layer formed on at least one surface of the steel sheet, an underlayer coating formed on the surface of the zinc-based plating layer, and an organic resin coating containing hypophosphite formed on the underlayer coating, the organic resin coating having a hypophosphite content of 10 to 50 mass % and a coating weight of hypophosphite of 0.01 to 2 g / m 2 A zinc-based plated steel sheet comprising:
5. A steel sheet having a tensile strength of 1180 MPa or more, a zinc-based plating layer formed on at least one surface of the steel sheet, an underlayer coating containing hypophosphite formed on the surface of the zinc-based plating layer, and an organic resin coating containing hypophosphite formed on the underlayer coating, wherein the hypophosphite contents in the underlayer coating and the organic resin coating are each 10 to 50 mass %, and the total coating weight of hypophosphite in the underlayer coating and the organic resin coating is 0.01 to 2 g / m 2 A zinc-based plated steel sheet comprising:
6. A zinc-based plated steel sheet comprising a steel sheet having a tensile strength of 1180 MPa or more, a zinc-based plating layer formed on at least one surface of the steel sheet, and an inorganic coating containing hypophosphite formed on the surface of the zinc-based plating layer, the inorganic coating containing hypophosphite alone as a coating component, and the amount of hypophosphite deposited being 0.01 to 2 g / m2.
7. A zinc-based plated steel sheet comprising a steel sheet having a tensile strength of 1180 MPa or more, a zinc-based plating layer formed on at least one surface of the steel sheet, an underlayer coating containing hypophosphite formed on the surface of the zinc-based plating layer, and an organic resin coating formed on top of the underlayer coating, wherein the underlayer coating contains hypophosphite alone as a coating component, and the amount of hypophosphite deposited is 0.01 to 2 g / m2.
8. A zinc-based plated steel sheet comprising a steel sheet having a tensile strength of 1180 MPa or more, a zinc-based plating layer formed on at least one surface of the steel sheet, an underlayer coating containing hypophosphite formed on the surface of the zinc-based plating layer, and an organic resin coating containing hypophosphite formed on an upper layer of the underlayer coating, wherein the underlayer coating contains hypophosphite alone as a coating component, the content of hypophosphite in the organic resin coating is 10 to 50 mass %, and the total adhesion amount of hypophosphite in the underlayer coating and the organic resin coating is 0.01 to 2 g / m2.
9. 9. The zinc-based plated steel sheet according to any one of claims 2 to 5, 7 and 8, characterized in that the organic resin constituting the organic resin coating is one or more selected from the group consisting of epoxy resin, acrylic resin, urethane resin, ethylene resin, phenol resin, polyester resin, fluororesin, polyolefin resin and epoxy ester resin.
10. 9. The zinc-based plated steel sheet according to any one of claims 1 to 8, characterized in that the hypophosphite comprises at least one selected from the group consisting of sodium hypophosphite, potassium hypophosphite, nickel hypophosphite, calcium hypophosphite, magnesium hypophosphite and manganese hypophosphite.
11. The substrate is a zinc-based plated steel sheet having a tensile strength of 1180 MPa or more and a zinc-based plating layer formed on at least one surface of the steel sheet, and a treatment solution containing a hypophosphite (excluding treatment solutions containing a hypophosphite and a magnesium compound) is applied to the surface of the zinc-based plating layer. ) is applied to the substrate and dried to form a film containing hypophosphite (excluding films containing hypophosphite and a magnesium compound), and the amount of hypophosphite attached in the film is 0.01 to 2 g / m 2 1. A method for producing a zinc-based plated steel sheet, comprising the steps of:
12. The present invention uses a zinc-based plated steel sheet having a tensile strength of 1180 MPa or more and a zinc-based plated layer formed on at least one surface of the steel sheet as a substrate, and applies an organic resin-based or inorganic-based treatment liquid containing hypophosphite to the surface of the zinc-based plated layer and dries the treatment liquid to form an organic resin-based or inorganic-based film containing hypophosphite, and the content of hypophosphite in the film is 10 to 50 mass % and the amount of hypophosphite attached is 0.01 to 2 g / m. 2 1. A method for producing a zinc-based plated steel sheet, comprising the steps of:
13. A zinc-based plated steel sheet having a tensile strength of 1180 MPa or more and a zinc-based plating layer formed on at least one surface of the steel sheet is used as a substrate, a treatment liquid containing hypophosphite is applied to the surface of the zinc-based plating layer and dried to form an underlayer coating containing hypophosphite, and then an organic resin-based treatment liquid is applied to the surface of the underlayer coating and dried to form an organic resin coating on the upper layer of the underlayer coating, and the hypophosphite content in the underlayer coating is 10 to 50 mass % and the deposition amount of hypophosphite is 0.01 to 2 g / m 2 1. A method for producing a zinc-based plated steel sheet, comprising the steps of:
14. The present invention uses a zinc-based plated steel sheet having a tensile strength of 1180 MPa or more and a zinc-based plated layer formed on at least one surface of the steel sheet as a substrate, and forms an underlayer coating by applying a treatment liquid to the surface of the zinc-based plated layer and drying the same, and then forms an organic resin coating containing hypophosphite on the upper layer of the underlayer coating by applying an organic resin-based treatment liquid containing hypophosphite to the surface of the underlayer coating and drying the same, and the content of hypophosphite in the organic resin coating is 10 to 50 mass % and the amount of hypophosphite attached is 0.01 to 2 g / m 2 1. A method for producing a zinc-based plated steel sheet, comprising the steps of:
15. A zinc-based plated steel sheet having a tensile strength of 1180 MPa or more and a zinc-based plating layer formed on at least one surface of the steel sheet is used as a substrate, a treatment liquid containing hypophosphite is applied to the surface of the zinc-based plating layer, and dried to form an underlayer coating containing hypophosphite, and then an organic resin-based treatment liquid containing hypophosphite is applied to the surface of the underlayer coating, and dried to form an organic resin coating containing hypophosphite on the upper layer of the underlayer coating, wherein the hypophosphite contents in the underlayer coating and the organic resin coating are each 10 to 50 mass % and the total deposition amount of hypophosphite in the underlayer coating and the organic resin coating is 0.01 to 2 g / m 2 1. A method for producing a zinc-based plated steel sheet, comprising the steps of:
16. A method for producing zinc-based plated steel sheet, comprising: a base material being a zinc-based plated steel sheet having a tensile strength of 1180 MPa or more and a zinc-based plating layer formed on at least one surface of the steel sheet; applying an inorganic treatment liquid containing hypophosphite to the surface of the zinc-based plating layer and drying it to form an inorganic coating containing hypophosphite, the inorganic coating containing hypophosphite alone as a coating component, and the amount of hypophosphite deposited being 0.01 to 2 g / m2.
17. A method for manufacturing a zinc-based plated steel sheet, comprising: a base material being a zinc-based plated steel sheet having a tensile strength of 1180 MPa or more and a zinc-based plating layer formed on at least one surface of the steel sheet; a treatment liquid containing hypophosphite is applied to the surface of the zinc-based plating layer and dried to form an underlayer coating containing hypophosphite; and an organic resin treatment liquid is applied to the surface of the underlayer coating and dried to form an organic resin coating on top of the underlayer coating, the underlayer coating containing hypophosphite alone as a coating component, and the amount of hypophosphite deposited is 0.01 to 2 g / m2.
18. A method for manufacturing a zinc-based plated steel sheet, comprising: a base material being a zinc-based plated steel sheet having a tensile strength of 1180 MPa or more and a zinc-based plating layer formed on at least one surface of the steel sheet; a treatment liquid containing hypophosphite is applied to the surface of the zinc-based plating layer and dried to form an underlayer coating containing hypophosphite; and an organic resin-based treatment liquid containing hypophosphite is applied to the surface of the underlayer coating and dried to form an organic resin coating containing hypophosphite on an upper layer of the underlayer coating, the underlayer coating containing hypophosphite alone as a coating component, the content of hypophosphite in the organic resin coating being 10 to 50 mass %, and the total deposition amount of hypophosphite in the underlayer coating and the organic resin coating being 0.01 to 2 g / m2.
19. 19. The method for producing a zinc-based plated steel sheet according to any one of claims 12 to 15, 17 and 18, characterized in that the organic resin constituting the organic resin coating is one or more selected from the group consisting of epoxy resin, acrylic resin, urethane resin, ethylene resin, phenolic resin, polyester resin, fluororesin, polyolefin resin and epoxy ester resin.
20. 19. The method for producing a zinc-based plated steel sheet according to any one of claims 11 to 18, characterized in that the hypophosphite comprises at least one selected from the group consisting of sodium hypophosphite, potassium hypophosphite, nickel hypophosphite, calcium hypophosphite, magnesium hypophosphite and manganese hypophosphite.
Citation Information
Patent Citations
Hot dip galvanized steel sheet having superior resistance to blackening, corrosion and scratch and its manufacture
JP1986253378A
Method of preventing hydrogen brittlenes and steel materials obtained by this method
JP1990021970A
Steel sheet superior in delayed fracture resistance
JP2003041384A
HIGH STRENGTH STEEL SHEET HAVING MAXIMUM TENSILE STRENGTH OF >=900 MPa AND HAVING SATISFACTORY DUCTILITY AND DELAYED FRACTURE RESISTANCE, METHOD FOR PRODUCING HIGH STRENGTH COLD ROLLED STEEL SHEET, AND METHOD FOR PRODUCING HIGH STRENGTH GALVANIZED STEEL SHEET
JP2011111671A
Delayed fracture resistant chemically treated steel material and structure using the same
JP2015209585A